Thromboelastometry: A contribution to perioperative free-flap management. Issue 7 (September 2015) - Wikner, Johannes; Beck-Broichsitter, Benedicta E.; Schlesinger, Saskia; Schön, Gerhard; Heiland, Max; Assaf, Alexandre Thomas; Rashad, Ashkan; Riecke, Björn; Heckel, Kai
Abstract Background Microvascular tissue transfer is a fundamental part of reconstructive surgery. Different perioperative anticoagulation regimens exist, influencing hemostatic parameters. Since bleeding and thrombosis are major reasons for revision procedures and flap loss, current practice regarding anticoagulative treatment needs further refinement. Thromboelastometry has been demonstrated as worthwhile in the determination of alterations of the anticoagulation cascade. We evaluated this aspect of thromboelastometry for free flap surgery. Methods Thirty-five patients undergoing free-flap surgery were enrolled in this study. Blood samples were obtained at three time points: at the beginning of surgery, at time of anastomosis and after 24 h. At each time point, thromboelastometry with special regard to clotting times for the intrinsic and extrinsic paths of coagulation was immediately performed. Global coagulation markers and clinical parameters were collected simultaneously. Results Hemostatic changes were deducible using thromboelastometry perioperatively. Measured parameters differed significantly over time (p < 0.05). Heparin therapy showed a significant effect on the measured slope of INTEM-clotting times (p < 0.001). Altered values of thromboelastometry suggested non-inferiority to standard testing. Neither standard testing nor thromboelastometry were capable of predicting adverse events such as thrombosis, bleeding or flap loss (p > 0.05). Conclusions Thromboelastometry monitors hemostatic effects almost in real-time and could serve as a supplementary tool in microvascular tissue transfer once its use has been standardized. The utilization of thromboelastometry allows for assessment of the anticoagulation needs of individual patients undergoing free flap surgery, which is frequently accompanied by hemostatic changes in the perioperative setting. Our findings implicate further validation of thromboelastometry in free-flap surgery.